Efektivitas Aktivator Alkali Potassium Hidroksida Dan Abu Sekam Padi Terhadap Kuat Tekan Beton Geopolimer - Naufal, Muhammad; Sariman, Syahrul; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Geopolymer concrete is a concrete product whose binding reaction is a polymerization reaction. In this reaction Aliminium (Al) and Silica (Si) have an important role because Aluminum and Silica will produce AlO2 and SiO4. The alkaline activators used are Sodium Hydroxide (NaOH), Potassium Hydroxide (KOH) and Sodium Silicate (Na2SiO3). Constituent material on. Geopolymer concrete consists of coarse aggregate, fine aggregate and water. NaOH is dissolved with distilled water, then mixed with Na2SiO3. In the research process using the curing method by wrapping for 28 days. The compressive strength values of concrete using 95%, 90%, 85% ASP variations of NaOH activators were 21.42 Mpa, 20.10 Mpa, 16.04 Mpa. The compressive strength values of concrete using KOH activators with variations of ASP 95%, 90%, 85% were 26.86 Mpa, 22.74 Mpa, 18.40 Mpa. The use of KOH as an aktivator with Variation of Rice Husk Ash experienced an increase in compressive strength compared to using the NaOH activator.